Mesoporous single-crystal-like TiO2 mesocages threaded with carbon nanotubes for high-performance electrochemical energy storage. (May 2017) - Peng, Yiting; Le, Zaiyuan; Wen, Meicheng; Zhang, Dieqing; Chen, Zheng; Wu, Hao Bin; Li, Hexing; Lu, Yunfeng
Abstract: A novel nanocomposite based on mesoporous single-crystalline TiO2 particles (TiO2 mesocages) threaded with carbon nanotubes (CNTs) has been successfully synthesized via a facile solvothermal method. The unique hybrid architecture endows the nanocomposite with facile ion and electron transport pathways, abundant active surface sites and high structure robustness. As a result, remarkable electrochemical lithium storage properties in terms of high capacity, excellent rate capability and ultra-stable long-term cycling performance have been achieved by the CNTs-threaded TiO2 mesocages. Graphical abstract: Mesoporous single-crystalline TiO2 mesocages threaded with carbon nanotubes synthesized via a facile solvothermal method possess facile ion and electron transport pathways, abundant active surface sites and high structure robustness. Such nanocomposite exhibits remarkable electrochemical lithium storage properties in terms of high capacity, excellent rate capability and ultra-stable long-term cycling performance. Highlights: Single-crystal-like TiO2 mesocages with CNTs enable fast kinetics and surface charge storage. Threading CNTs through sub-micrometer size TiO2 provide robust and intimate interfaces. Unique architecture offers facile conductivity, high structural robustness and packing density.